REVITALISASI SDM DALAM PROSES TRANSFORMASI PT KAI: KAJIAN TERHADAP KEPEMIMPINAN, LINGKUNGAN KERJA, DAN KINERJA KARYAWAN - Ludfiono; Ahmad Badawi Saluy (Jurnal Ekonomi dan Manajemen, 2025)
Organizational transformation is a critical strategy for companies to respond to dynamic and ever-changing environments. PT Kereta Api Indonesia (Persero) serves as a notable example of a public organization that has successfully implemented a comprehensive transformation since 2009, placing human resources (HR) at the center of its reform efforts. This study aims to examine the roles of leadership, HR revitalization, work environment, and employee performance in supporting the organizational transformation process by employing a literature review approach based on journals, theses, and other relevant scholarly sources. The findings indicate that transformational leadership plays a pivotal role in shaping a new work culture, which is further reinforced through HR revitalization initiatives such as training, competency-based recruitment, and strengthened work systems. A conducive work environment supports the internalization of organizational values such as excellent service and professionalism. Employee performance serves both as an indicator and a tangible outcome of a successful transformation. This study underscores that the synergy between leadership, HR, and the work environment forms the foundation for achieving sustainable organizational transformation.